Evolution of Qur’anic Exegetical Methods in Aceh through Hermeneutic and Sociological Lenses - Amin, Muhammad; Anzaikhan, M.; Armainingsih, Armainingsih; Nurkholis, Nurkholis; Zubir, Zubir (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
Qur’anic interpretation in Aceh has developed in tandem with shifting social, political, and cultural conditions, producing distinct exegetical profiles across historical periods. This study traces the evolution of interpretive methods in Aceh through hermeneutic and sociological lenses in order to show how the sacred text is understood, interpreted, and enacted in communal life. Using a qualitative design, the analysis applies a hermeneutic sociological approach to primary sources that include Abdurrauf as Singkili’s Tarjuman al Mustafid and contemporary Acehnese tafsir and sermon materials, supported by academic secondary literature. Findings indicate a trajectory from a Sufi and fiqh oriented profile that foregrounds spiritual and normative dimensions, to a rational modern turn disseminated through sermons and print media, and finally to a hermeneutic sociological approach that places the text in active dialogue with post conflict realities and the formalization of Sharia through qanun. The results show that methodological change is not linear but context responsive and that tafsir functions as a social practice that mediates norms, education, and public policy.